Effects of tidal torques on 1I/2017 U1 (‘Oumuamua) - Kwiecinski, J; Krause, A; Van Gorder, R (Elsevier, 2018)
As observations of ‘Oumuamua were collected well into the outbound component of its hyperbolic orbit, it is not obvious what effects Sol had on its rotational dynamics. Therefore, we simulate ‘Oumuamua as a prolate spheroid and triaxial ellipsoid of uniform mass density and show that the experimentally observed angular velocities remain largely unchanged during ‘Oumuamua’s flyby, supporting previous work suggesting that, in the absence of a collision during its interstellar journey, the asteroid was tumbling in the same manner as when it left its original solar system.